Mesoporous Silica Nanoparticles Based Antigens and Nucleic Acids Delivery: A Review - Dilebo, Jemal (Asian Journal of Pharmaceutical Research and Development, 2020)
Mesoporous silica nanoparticles (MSN) have been explored for the delivery of small molecule drugs, antigens, and nucleic acids because of their large surface area, pore volume, amenability of their surface for functionalization, stable mesoporous structure, and biocompatibility. Biomoecules loading capacitites, release and target cell accumulation efficiencies have been improved for both antigen and nucleic acid delivery by the synthesis of large-pore MSN, dendritic MSN, hollow-core MSN, and multifunctional MSN. This article overview the major advances in the use of MSN for delivery of antigens and therapeutic nucleic acids such as DNA, siRNA, and miRNA aimed for treatment of various diseases.